Maori media production, civic journalism and the foreshore and seabed controversy in Aotearoa - Darrin Hodgets (Asia Pacific Network, 2005)
This article explores the social significance of increased media production by Maori in Aotearoa/New Zealand as an opportunity for challenging a tendency in mainstream journalism to promote Pakeha perspectives. The analysis focuses on the recent documentary Hikoi, which was initiated by two young Maori women as a challenge to media framing of Maori protests as 'unjustified' and 'disruptive' acts. We argue that this documentary illustrates the potential for civic journalists to broaden public deliberations regarding political issues such as the foreshore and seabed controversy.